Food consumption and nutritional adequacy in Brazilian children: a systematic review - Carvalho,Carolina Abreu de (2015)
OBJECTIVE: To perform a review of studies of food consumption and nutritional adaptation in Brazilian infants pointing the main findings and limitations of these studies. DATA SOURCE: The articles were selected from Literatura Latino-Americana e do Caribe em Ciências da Saúde (Lilacs) (Latin-American and Caribbean Literature in Health Sciences), Scientific Electronic Library Online (SciELO) and Science Direct in Portuguese and in English. The descriptors were: ''food consumption'', ''nutritional requirements'', ''infant nutrition'' and ''child''. The articles selected were read by two evaluators that decided upon their inclusion. The following were excluded: studies about children with pathologies; studies that approached only food practices or those adaptation of the food groups or the food offert; and studies that did not utilize the Dietary Reference Intakes (DRI). DATA SYNTHESIS: Were selected 16 studies published between 2003 and 2013. In the evaluation of the energy consumption, four studies presented energetic consumption above the individual necessities. The prevalence of micronutrients inadequacy ranged from 0.4% to 65% for iron, from 20% to 59.5% for vitamin A, from 20% to 99.4% for zinc, from 12.6% to 48.9% for calcium and from 9.6% 96.6% for vitamin C. CONCLUSIONS: The food consumption of Brazilian infants is characterized by high frequencies of inadequacy of micronutrients consumption, mainly iron, vitamin A and zinc. These inadequacies do not exist only as deficiencies, but also as excesses, as noted for energetic consumption.